Analisis Data Panel pada Tingkat Pengangguran Terbuka Kabupaten/Kota di Pulau Jawa - Hasih Pratiwi; Ardina Nilam Prawastyorini; Sugiyanto Sugiyanto (Department of Mathematics, Hasanuddin University, 2019)
Unemployment rate is the percentage of the number of unemployed to the total labor force, it has become some problems in economic development. The aim of this study is to choose the best model between common, fixed, and random effects in modeling open unemployment rate of regency/city in Java. It based on open unemployment rate with several influence factors in Java Island 2010-2016 which are panel data types. The best model choosen based on the results of the Chow test and Hausman test. The fixed effect model was obtained as the best model with a value of 79,26 percent.